[The Big squeeze ; Saving grace ; South of Manila - Lazaro, Cheche (Quezon City Probe Productions, 1990)
Tackles oil prices which increased by 50 and were rolled back ; export industry ; and interviews with singer and performer, Jo Awayan.
The big squeeze (14 min.) -- Saving grace (15 min.) -- South of manila (15 min.).
VHS.
Keywords: Awayan, Jo -- Interviews; Petroleum products -- Philippines; Exports -- Philippines